Model of innovative development of Kazakhstan considering the development of the innovation process. (Journal of Economic Research & Business Administration, 2015)
Perspectives of innovative development of Kazakhstan were reflected. We proposed to use the integration approach. We proposed the formation of the innovation process. The author offered a cluster approach, namely the formation of regional innovation clusters. Dan conceptual apparatus innovation cluster, regional innovation clusters, showing features. We offered conceptual apparatus of innovation cluster and regional innovation clusters and ivestigated its features. We took Pavlodar region as an example, where chemical, railway, petrochemical cluster and a cluster of nonferrous metallurgy are developed. A scheme of transformation of existing clusters in innovation clusters was presented. We elaborated the structure of the Centre for the formation and coordination of activity of regional innovation clusters and presented the purpose, tasks, activities, functions of the departments. Using an integrated approach we proposed to form a regional innovation clusters, whereby the innovation process will be activated, thus allowing to form a "traditional" model of innovative development of the economy
Keywords: innovation process; integration; innovation development; regional innovation cluster and model